1996
DOI: 10.1006/cbir.1996.0018
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cell Migration in the Intestine

Abstract: Despite significant advances in our understanding of the roles of the cytoskeleton and matrix receptors in cell locomotion, derived largely from in vitro studies on the movement of epithelial cell sheets and isolated cells, the mechanism of epithelial cell migration in the adult intestine remains an enigma. The primary function of the epithelial cell cytoskeleton seems to be in the maintenance of the apical region of the epithelium facing the gut lumen. There we find the brush border, with its associated enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
125
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(132 citation statements)
references
References 0 publications
2
125
0
5
Order By: Relevance
“…The enrichment of these functions is in agreement with previous studies that have shown intestinal development gene expression profiles during early life affected by maternal nutrition during gestation (Meyer et al, 2013). Our results also reported different functions related to inhibition in cell migration; these functions should be interpreted as regular development as opposed to the process of migration that in most cases is associated with an injury or inflammation response (Heath, 1996). Survival of connective tissue was reported to be in an activation state and may represent positive structural development of the intestinal tract (Ishizuya-Oka and Shimozawa, 1992).…”
Section: Discussionsupporting
confidence: 92%
“…The enrichment of these functions is in agreement with previous studies that have shown intestinal development gene expression profiles during early life affected by maternal nutrition during gestation (Meyer et al, 2013). Our results also reported different functions related to inhibition in cell migration; these functions should be interpreted as regular development as opposed to the process of migration that in most cases is associated with an injury or inflammation response (Heath, 1996). Survival of connective tissue was reported to be in an activation state and may represent positive structural development of the intestinal tract (Ishizuya-Oka and Shimozawa, 1992).…”
Section: Discussionsupporting
confidence: 92%
“…Early mucosal restitution, as manifest by the rapid resealing of superficial wounds secondary to cell migration is an important primary repair modality, critical to preserving GI mucosal integrity [17][18][19][20]. NSAIDs contribute to ulcer formation and delay ulcer healing by inhibiting intestinal epithelial cell migration and mucosal restitution [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Superficial mucosal defects typically are repaired rapidly by migration of epithelial cells into the defect from the periphery of the wound. This process, called mucosal restitution, is a primary repair modality in the GI tract and is critical to preserving mucosal integrity and to suppressing ulceration [17][18][19][20]. Restitution occurs within minutes to hours following injury in vivo or in vitro, because this process requires cell migration but not cell proliferation or differentiation [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…85, 2011 NOTES 7945 nal tissue, which has the highest turnover rate of all adult mammalian tissues (24,65). This speculation is also supported by the fact that the fastest-evolving nonenterovirus, HPeV, frequently infects enteric tissue (15,56) and was once classified as an enterovirus (15,56).…”
mentioning
confidence: 98%